FIN SANDY CONCRETE REINFORCED WITH MACRO POLYPROPYLENE FIBER FOR RURAL AND DESERT HOUSING - RAHMA, AFIF (Journal of Duhok University, 2023)
with biomaterial fibers, where the latter is characterized by mechanical defects such as the low strength, the water degradation and the air erosion, as well as the continuous deformation related to the self-compression and unlimited subsidence of the bearing surface soil. The designed concrete is composed of fine sand, cement in small quantities and polypropylene fibers available on the daily market. This material is easy to form due to the availability of fine sand in nature and the possibility of its production without much skill; in the same time, it is make at a low cost and short implementation time, unlike earth concrete where it needs time to dry and acquire the appropriate strength. Laboratory work has shown good results as the light density, the large ductility and an acceptable strength capacity of this material.